2007
DOI: 10.1080/03235400600586781
|View full text |Cite
|
Sign up to set email alerts
|

Induction of systemic resistance to bacterial blight caused byXanthomonas campestrispv.malvacearumin cotton by leaf extract from a medicinal plant zimmu (Allium sativumL. × Allium cepaL.)

Abstract: Induction of systemic resistance to bacterial blight caused by Xanthomonas campestris pv. malvacearum in cotton by leaf extract from a medicinal plant zimmu (Allium sativum L. 6 Allium cepa L.) Abstract Aqueous extract (10%) from leaves of zimmu (Allium sativum L. 6 Allium cepa L.) when applied as foliar spray to first and second leaves of cotton plants induced systemic resistance in third and fourth leaves to a challenge infection with Xanthomonas campestris pv. malvacearum and reduced the number of lesions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…The resistant genotypes (LE996 and Seijima Jeisei) showed maximum PAL activity when compared to susceptible ones under challenge inoculation. These results are well correlated with the findings of Geetha et al (2005) and Satya et al (2006).…”
supporting
confidence: 93%
“…The resistant genotypes (LE996 and Seijima Jeisei) showed maximum PAL activity when compared to susceptible ones under challenge inoculation. These results are well correlated with the findings of Geetha et al (2005) and Satya et al (2006).…”
supporting
confidence: 93%
“…Cotton plants treated with the leaf extract of zimmu (Allium sativum L. × Allium cepa L.) showed higher activities of PAL, POX and PPO and high concentrations of phenolic compounds that contributed to an increase in resistance against X. campestris pv. malvacearum infection (Satya et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The plant extracts that contain many of these metabolites have been investigated for their increased resistance against pathogens infection, such as the zimmu extract (Allium sativum L. x Allium cepa L.) in the control of Xanthomonas campestris pv. malvacearum on cotton (Satya et al, 2007) and Lasiodiplodia theobromae and Colletotrichum musae on banana (Sangeetha et al, 2013 ). Extracts of Datura metel increased rice resistance against Rhizoctonia solani and X. oryzae pv.…”
Section: Introductionmentioning
confidence: 99%
“…oryzae in rice has been investigated (Kagale et al, 2004) and it was found that foliar application of leaf extract effectively reduced the incidence of sheath blight and bacterial blight of rice. Satya et al (2007) applied aqueous leaf extract of zimmu (Allium sativum L. x Allium cepa L.) to first and second leaves cotton plants that induced systemic resistance in third and fourth leaves and reduced the number of lesions by up to 73% after challenged infection with Xanthomonas campestris pv. malvacearum compared with water-treated control plants.…”
Section: Figure 2 Mean Comparison Of Percentage Reduction In Ascochymentioning
confidence: 99%